Mobility, exposure, and epidemiological timelines of COVID-19 infections in China outside Hubei province - Xiao Fan Liu (Nature Portfolio, 2021)
Measurement(s) Epidemiological Factors • exposure • Demographics • travel history • Quarantine • Symptom Onset • Symptom • Hospitalization • Viral Infection Technology Type(s) digital curation • manual coding Sample Characteristic - Organism Homo sapiens Sample Characteristic - Location China Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13567553